2010
DOI: 10.1111/j.1365-2583.2010.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased detoxification genes and genome size make the human body louse an efficient model to study xenobiotic metabolism

Abstract: The human body louse, Pediculus humanus humanus, has one of the smallest insect genomes, containing ~10,775 annotated genes (Kirkness et al. 2010). Annotation of detoxification [cytochrome P450 monooxygenase (P450), glutathione-S-transferase (GST), esterase (Est), and ATP-binding cassette transporter (ABC transporter)] genes revealed that they are dramatically reduced in P. h. humanus compared to other insects except for Apis mellifera. There are 37 P450, 13 GST and 17 Est genes present in P. h. humanus, appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 71 publications
5
55
0
3
Order By: Relevance
“…Of the three classes, only the neuro/developmental one seems to be consistently monophyletic but always with low bootstrap support. Genomic sequencing has shown that all esterase classes and most clades are represented in several insect species, although the number of genes in each clade varies widely (Claudianos et al, 2006;Lee et al, 2010;Niranjan Reddy et al, 2012;Oakeshott et al, 2010;Ramsey et al, 2010;Tsubota and Shiotsuki, 2010a;Yu et al, 2009). Apart from the pheromone/hormone processing class where a smaller number of genes were found in R. prolixus, in the other two classes the number of genes mirrors those of other vector species studied (Table 1).…”
Section: Esterasesmentioning
confidence: 64%
“…Of the three classes, only the neuro/developmental one seems to be consistently monophyletic but always with low bootstrap support. Genomic sequencing has shown that all esterase classes and most clades are represented in several insect species, although the number of genes in each clade varies widely (Claudianos et al, 2006;Lee et al, 2010;Niranjan Reddy et al, 2012;Oakeshott et al, 2010;Ramsey et al, 2010;Tsubota and Shiotsuki, 2010a;Yu et al, 2009). Apart from the pheromone/hormone processing class where a smaller number of genes were found in R. prolixus, in the other two classes the number of genes mirrors those of other vector species studied (Table 1).…”
Section: Esterasesmentioning
confidence: 64%
“…We can test this hypothesis by comparing the compositions of the three gene families in M. sexta (which has a wide host range across the Solanaceae) with the corresponding data from published annotations for these three enzyme families for two other lepidopterans: the silkworm B. mori (which is a specialist feeder on mulberry (International Silkworm Genome, Consortium, 2008)) and diamondback moth P. xylostella (which has a wide host range across the Brassicaceae (You et al, 2013)). Table S14 shows that the total number of genes in the three families across the three species (181, 228, and 168 genes for B. mori, M. sexta , and P. xylostella , respectively) shows more limited variation than observed in some of the inter-order comparisons on which the hypothesis was based, and which showed aggregate differences in gene numbers of 2–4 fold across orders (Claudianos et al, 2006; Lee et al, 2010; Oakeshott et al, 2010; Sadd et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the comparison analysis of the purified GSTs from three field collected populations of P. citri suggested that GSTs could be partially associated with the pyridaben susceptibility of P. citri. However, the total number of cytosolic GSTs genes of D. melanogaster, A. gambiae, Pediculus humanus humanus L. (Phthiraptera: Pediculidae) and Apis mellifera L. (Hymenoptera: Apidae), were founded for 37, 28, 11 and 8, respectively (Lee et al 2010). To date, it is not clear how many GSTs genes were existed in spider mites.…”
Section: Discussionmentioning
confidence: 98%